Deteksi Dini Kanker Serviks Melalui Pemeriksaan Inspeksi Visual Asam Asetat (IVA: Early Detection of Cervical Cancer Through Visual Inspection with Acetic Acid (VIA) - Nurarifah, Nurarifah; Tampuyak, Irawati; Sinurat, Diana; Mangemba, Dg.; Ra’bung, Alfrida Semuel (Jurnal Pengabdian Masyarakat Lentora, 2022)
Introduction: Cervical cancer does not cause symptoms at an early stage so that a person does not realize that they already have cancer so that it is detected at an advanced stage when cancer cells have metastasized outside the cervix. Women who have had sexual intercourse are at risk of cervical cancer, so it is very important to take early detection measures through IVA examinations. Purpose: This community service activity is for early detection of cervical cancer through IVA examination. Method: This community service activity is by conducting an IVA examination. This activity was carried out on August 10, 2022. The target audience for this activity were women of childbearing age who were members of the Dharma Wanita Association of the Ministry of Religion of Banggai Regency as many as 22 people. Results: The IVA examination of all WUS was negative and showed no symptoms of cervical cancer. Conclusion: The IVA examination activity for detecting cervical cancer can be used as a health promotion program to facilitate WUS in carrying out reproductive health checks.